Demographic factor of replacement of employees with PhD degrees in the Republic of Belarus - Boreiko, Snezhana A. (Journal of the Belarusian State University. Sociology, 2022)
Based on the analysis of statistical data, the determining influence of the demographic factor on the level of replacement of employees with PhD degrees in the economy is substantiated. It is established that the reduction in the number of persons studying at the postgraduate school of the Republic of Belarus is of a natural nature. This trend is due to the processes of reducing the number of young people aged 17 to 24 years, who form the basis of students. Due to the reduction in the number of young people, there is an annual decrease in the number of students who have a decisive influence on the volume of training of employees with PhD degrees (there are 13.9 graduate students per 1 thousand students). Based on demographic statistics data, as well as using classification by year of birth, the recruitment of students and postgraduates to higher educational institutions until 2030 is predicted.
Keywords: the system of postgraduate education; employees with PhD degrees; replacement of employees; efficiency of the postgraduate system; teaching staff of universities; factors of replacement of employees with PhD degrees